2022
DOI: 10.1002/chem.202201449
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Mg2+‐Free State in Nucleotide Exchange of Oncogenic K‐Ras Mutants

Abstract: For efficient targeting of oncogenic K-Ras interaction sites, a mechanistic picture of the Ras-cycle is necessary. Herein, we used NMR relaxation techniques and molecular dynamics simulations to decipher the role of slow dynamics in wild-type and three oncogenic P-loop mutants of K-Ras. Our measurements reveal a dominant two-state conformational exchange on the ms timescale in both GDPand GTP-bound K-Ras. The identified low-populated higher energy state in GDP-loaded K-Ras has a conformation reminiscent of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 85 publications
2
8
0
Order By: Relevance
“…These results suggest that the HBIs of V29 and D30 in the SW I with GDP are highly unstable. The aforementioned interaction sites of GDP and NRAS agree well with the GDP binding spots identified in the work of Johnson et al [ 29 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggest that the HBIs of V29 and D30 in the SW I with GDP are highly unstable. The aforementioned interaction sites of GDP and NRAS agree well with the GDP binding spots identified in the work of Johnson et al [ 29 ].…”
Section: Resultssupporting
confidence: 87%
“…As shown in Figure 1 A, SW I, SWII, and the P-loop encircle a binding pocket of GTP or GDP. The X-ray and NMR experiments by Pálfy et al revealed that the conformations of the switch domains from the RAS proteins are highly affected by G12 mutations [ 28 , 29 ]. Mutations lead to large conformational changes in the two switches, SW I and SW II, which yield a significant effect on the activity of NRAS [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ras oncoproteins can exist in different nucleotide-bound and mutant forms in cells, all of which are inherently flexible 7,29–33,54,55 populating a diverse set of conformations including many that possess druggable pockets unobserved in the ground structures. To date, studies that took advantage of the cryptic pockets 10,13–15,38,56 for targeting have significantly advanced the therapeutics development against Ras and proved covalent modification a feasible strategy for direct inhibition of Ras(G12C)·GDP.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Conformational exchange was also captured by relaxation-based NMR in the inactive GDP-bound state, which however occurs on a much faster timescale. 28 Previous molecular dynamics and enhanced sampling simulations 7,11,29–33 suggest that the cryptic pockets can commonly pre-exist in different nucleotide-bound and mutant forms. However, it remains unclear how the mutations and activation states alter the “invisible” vulnerable conformers of Ras leading to the differential druggabilities noted in recent drug development efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies on RAS proteins by solution-state NMR have shown the presence of allostery connecting the effector and allosteric lobes using chemical shift perturbations 5 , 19 and relaxation dispersion experiments 20 22 , it is not clear how those observations can be translated to structural changes outside of the switch regions in KRAS in solution, which is the focus of our present NMR study. It had been shown that the dynamics of the HRAS isoform can be affected by using non-hydrolyzable GTP analogs 23 , and recent dynamic studies using GTP with HRAS 22 and with KRAS 24 showed that two different minor states of GTP-bound RAS can be produced under different experimental conditions. Interestingly, although HRAS and KRAS proteins have an identical primary sequence in the effector lobe, they display different structural features in the reported minor states, highlighting the complex dynamics of RAS proteins in solution.…”
Section: Introductionmentioning
confidence: 99%